2021
DOI: 10.1007/s10340-020-01322-7
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics and host specificity of Varroa destructor mites infesting eastern and western honeybees

Abstract: In a globalized world, parasites are often brought in contact with new potential hosts. When parasites successfully shift host, severe diseases can emerge at a large cost to society. However, the evolutionary processes leading to successful shifts are rarely understood, hindering risk assessment, prevention, or mitigation of their effects. Here, we screened populations of Varroa destructor, an ectoparasitic mite of the honeybee genus Apis, to investigate their genetic structure and reproductive potential on ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 66 publications
4
23
0
Order By: Relevance
“…Recent work has shown experimentally that gene flow between can occur between V. destructor populations on the two hosts in the native range [20]. This observation, together with migration between host species detected in this study provides a mechanism by which gene flow occursthrough occasional co-infestations by females from different populations.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Recent work has shown experimentally that gene flow between can occur between V. destructor populations on the two hosts in the native range [20]. This observation, together with migration between host species detected in this study provides a mechanism by which gene flow occursthrough occasional co-infestations by females from different populations.…”
Section: Discussionsupporting
confidence: 74%
“…mellifera belonged to the Korean K1 lineage, which was also found in one A. cerana sample (Figure 1B). We found three additional K1 mitotypes in China that were not previously reported on A. mellifera [20] (Table S1). We confirmed that the SNPs differentiating these K1 mitotypes were not artifacts of base calling by manually checking the read alignments.…”
Section: Cryptic Diversity In Mitogenomes Suggests Multiple Foundresses At the Origins Of The Host Switchmentioning
confidence: 67%
“…Throughout our Asian sampling sites, all V. destructor mitotypes on the new host (A. mellifera) belonged to the Korean K1 lineage and was also found in one original host colony (Apis cerana) sample (Figure 1b). We found three additional K1 mitotypes in China that were not previously reported on A. mellifera (Lin et al, 2021) (Table S1). We confirmed that the SNPs differentiating these K1 mitotypes were not base-calling artefacts by manually checking the read alignments.…”
Section: Re Sultsmentioning
confidence: 67%
“…Recent work has shown experimentally that gene flow can occur between V . destructor populations on the two hosts in the native range (Lin et al, 2021). This observation, together with migration between host species detected in this study, provides a mechanism by which gene flow occurs—through occasional co‐infestations by females from different populations.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, by concatenating mitochondrial haplotype sequences, 18 haplotypes of V. destructor could be assigned to six haplogroups of V. destructor infesting A. mellifera and/or A. cerana . Recently, 14 additional haplotypes and three additional haplogroups (K2, J2, and C4) were identified in A. mellifera and/or A. cerana in China [ 64 ]. Due to a bottleneck event where a host switch from A. cerana to A. mellifera occurred, some variants of haplogroups K1 and J1 are exclusively identified in A. mellifera (e.g., K1-1/2, K1-4, K1-5, J1-1, and J1-6).…”
Section: Description Of Main Bee Pathogens and Molecular Methods For ...mentioning
confidence: 99%